Kiat jitu dalam pengawasan bibliografi untuk ketepatan dan ketersediaan informasi: Studi kasus taman pustaka di Universitas Negeri Surabaya - Rosanti, Febrin Eka (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2025)
Advances in information technology have had an impact on the management of university libraries, particularly in the processing of library materials and bibliographic control. The accuracy of bibliographic information is a key factor in facilitating information retrieval for library users. This study aims to identify strategies for bibliographic control to improve the accuracy and availability of information through the use of the Senayan Library Management System (SLiMS) application. This study employed a quantitative descriptive method using a survey technique, distributing questionnaires to 50 respondents consisting of librarians, technical staff, and faculty reading room managers at Surabaya State University. Data were collected using Google Forms and analyzed using descriptive statistical analysis. The results indicate that challenges in bibliographic management still exist, such as the failure to fully utilize SLiMS features, limited technical skills among librarians in developing application usage, and a lack of coordination among library units. Forty percent of respondents reported frequently encountering errors in bibliographic information, while 50% considered bibliographic oversight crucial for maintaining information accuracy. Strategies that can be implemented include regularly updating bibliographic data, verifying sources through cross-referencing, enhancing librarians’ competencies through training, strengthening collaboration among librarians, and optimizing SLiMS features in the cataloging and processing of library materials. Maximizing the implementation of SLiMS can improve librarians’ work efficiency, speed up the information retrieval process, and support the availability of accurate collections for the academic community.